The estimation of body center of mass kinematics in sport: proposal of a new protocol - Zago, Matteo; Mapelli, Andrea; Sidequersky, Fernanda V.; Lovecchio, Nicola; Ferrario, Virgilio F. (Italian Journal of Anatomy and Embryology, 2014)
The assessment of body Center of Mass (CoM) kinematics is an important measure in the analysis of sport movements since it is strictly related to balance and stability control [1]. Among the methods proposed to estimate CoM displacement, Segmental method appears to be suitable to investigate CoM kinematics in sport: human body is assumed as a system of rigid segments, and the whole-body CoM is calculated as the weighted average of the CoM of each segment. Each segment is defined by a set of landmarks, and their overall number represents a crucial choice in the protocol design process, being a compromise between accuracy and invasivity [2]. In the present study, using a motion capture system, we validated a protocol based upon the Segmental method, adopting a 14-landmarks anatomical model. Two sets of experiments were made. At first, our protocol was compared to the Ground Reaction Force method (GRF), accounted as a golden standard in CoM estimation. Subsequently, we investigated the aerial phase typical of many sports, comparing our protocol with: (1) an absolute reference, the parabolic regression of the vertical CoM trajectory during the time of flight; (2) two common approaches to estimate CoM kinematics in gait, known as Sacrum and Reconstructed Pelvis methods. Recognized accuracy indexes proved that the results obtained were comparable to the GRF; what is more, during the aerial phase our protocol showed to be significantly more accurate than the other two methods. The protocol assessed can therefore be adopted as a reliable tool for CoM kinematics estimation in further sport researches.